Variables Affecting Construction Cost Contingency: A Fuzzy Pairwise Methods Analysis - Mawariza, Putri Suci; Beatrix, Michella; Ramadhan, M Fathin (International Conference of Innovation and Community Engagement, 2025)
Contingency costs play an important role during the construction phase, as accurately estimating project contingency costs is one of the keys to successful project management. The improper use of contingency costs can lead to various problems. In determining contingency costs, practitioners have traditionally used a highly subjective approach. This study will discuss the weights of variables that influence the magnitude of contingency costs. The risk evaluation carried out focuses on risks related to project construction execution. The use of fuzzy logic with the weight risk analysis method is considered highly appropriate due to the many advantages of fuzzy logic analysis, which can help make risk analysis more objective. The study respondents consist of 12 experts from 6 reviewed construction projects. The analysis reveals that internal variables, such as Safety, Personnel, and Equipment and Material, have a greater impact on contingency costs compared to external variables. Safety ranks highest with a weight of 0.223, followed by Personnel at 0.209 and Equipment and Material at 0.171. External variables, including Natural and Social Variables, have lower weights of 0.101 and 0.073, respectively, indicating their smaller influence compared to internal factors